Brent Crude Oil Genesis and Development of the World's Most Important Oil Benchmark - Imsirovic, Adi. (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
In 2023, the Brent oil benchmark, a key international oil price marker for global crude oil underwent a substantial change. It incorporated another key benchmark, West Texas Intermediate oil from Midland, produced in the US and sold into European and Asian markets. Brent is used to set prices for over 70 per cent of global crude oil, so this fundamental change in the composition of the benchmarks is making some observers question its future development and even its survival. Lessons from the past are very important for the future, particularly in this case. This book revisits the history and genesis of the Brent oil benchmark and how it came to dominate the global oil market for oil. With chapters written by the individuals involved in trading and shaping the market, it brings the richness and texture to the usual historical narrative by recalling the events, companies and people who shaped its history. It introduces the historical background to the international oil markets and the reasons for a move from OPEC-set prices to oil benchmarks. It discusses the role of the North Sea in the international oil markets, as well as the role of the British government in the British national oil and gas monopoly (British National Oil Corporation or BNOC). The development of the North Sea oil, which coincided with the liberalisation policies in the UK and US, is also discussed, alongside the challenges of the oil exchange (International Petroleum Exchange) in London, the home of Brent and looks at the failures, attempted takeovers, and its eventual sale to the Intercontinental Exchange (ICE). It finally discusses the growing market ecosystem of the price reporting agencies (PRAs), which play a key role in establishing the value of the Brent benchmark. Adi Imsirovic is a Senior Research Fellow at the Oxford Institute for Energy Studies (OIES) and a director of Surrey Clean Energy, an energy consultancy. He has over 35 years of experience in the energy markets, most of it as an oil trader. He is also Fulbright Scholar and was an Adjunct Research Fellow at the Kennedy School of Government, Harvard. He has previously published the book Trading and Price Discovery for Crude Oils (2021) with Palgrave Macmillan.
Chapter 1: Adi Imsirovic, Historical background to the emergence of benchmarks and Brent in particular -- Chapter 2: Liz Bossley, UK State, BNOC, tax, markets, and Brent; first forward trades, optionality, terms, players -- Chapter 3: Colin Bryce, genesis of Brent trading, people, banks and players, products, deals and threats to the market -- Chapter 4: David Peniket, the IPE and Brent futures, all related to IPC/ ICE -- Chapter 5: Kurt Chapman, early Brent trading, storage, EFPs, CFDs, convergence of Dated and forward -- Chapter 6: Neil Fleming & Adrian Binks, the role of PRAs and early assessments, Platts and Argus and others -- Chapter 7: Adi Imsirovic, The future of Brent.
Keywords: Capital market; Power resources; Environmental economics; Energy policy; Energy and state; Capital Markets; Natural Resource and Energy Economics; Environmental Economics; Energy Policy, Economics and Management